Assessment of the cytolytic potential of a multivirus-targeted T cell therapy using a vital dye-based, flow cytometric assay - Koukoulias, Kiriakos; Papayanni, Penelope G.; Jones, Julia; Kuvalekar, Manik; Watanabe, Ayumi; Velazquez, Yovana; Gilmore, Sarah; Papadopoulou, Anastasia; Leen, Ann M.; Vasileiou, Spyridoula (Frontiers in Immunology, 2023)
Reliable and sensitive characterization assays are important determinants of the successful clinical translation of immunotherapies. For the assessment of cytolytic potential, the chromium 51 ( 51 Cr) release assay has long been considered the gold standard for testing effector cells.However, attaining the approvals to access and use radioactive isotopes is becoming increasingly complex, while technical aspects [i.e. sensitivity, short (4-6 hours) assay duration] may lead to suboptimal performance. This has been the case with our ex vivo expanded, polyclonal (CD4+ and CD8+) multivirus-specific T cell (multiVST) lines, which recognize 5 difficult-to-treat viruses [Adenovirus (AdV), BK virus (BKV), cytomegalovirus (CMV), Epstein Barr virus (EBV), and human herpes virus 6 (HHV6)] and when administered to allogeneic hematopoietic stem cell (HCT) or solid organ transplant (SOT) recipients have been associated with clinical benefit. However, despite mediating potent antiviral effects in vivo, capturing in vitro cytotoxic potential has proven difficult in a traditional 51 Cr release assay. Now, in addition to cytotoxicity surrogates, including CD107a and Granzyme B, we report on an alternative, vital dye -based, flow cytometric platform in which superior sensitivity and prolonged effector:target co-culture duration enabled the reliable detection of both CD4-and CD8-mediated in vitro cytolytic activity against viral targets without non-specific effects.